[Spanish translation] Unique features of physical education – a look at evaluation - Hein Mendes, Evandra (2022)
Evaluation of learning is integrated into all curricular components, including Physical Education, which deals with knowledge related to bodily culture, such as play and games, gymnastics, dancing, sports, wrestling and adventure activities. Seeking to better understand the characteristics of evaluative activities developed by physical education teachers, a descriptive study with a qualitative approach was carried out in the municipal territory of Marechal Cândido Rondon, State of Paraná, Brazil. The data were obtained by applying a semi-structured interview, which was considered valid in terms of language clarity, practical relevance and theoretical significance. Data collection took place between August and October, 2017, at school facilities. The data were analyzed qualitatively through the content analysis technique, and classified into evaluation functions, number of evaluations carried out per quarter, instruments/procedures, evaluation criteria and difficulties that came up during the evaluation process. The results showed that the evaluation process was both formal and informal, and was carried out through tests and papers, presented as a requirement of the school and focused on examining the appropriation of theoretical or conceptual knowledge, as well as through observation by the teacher. They were focused on analyzing the motion and technical evolution of each student, in addition to assessing their participation and involvement in the classroom. Generally speaking, the evaluation developed by the teachers sought to respond to the determinations of the school system and the unique features of knowledge related to body culture that are approached in this discipline.